WORKING MEMORY DALAM PEMBELAJARAN MATEMATIKA: SEBUAH KAJIAN TEORI - Vera Dewi Susanti; Dwijanto Dwijanto; Scolastika Mariani (Program Studi PGSD Universitas Flores, 2022)
The purpose of this study is to describe how short-term memory is in learning mathematics. This research method is a literature study. Literature study examines theories based on books, articles, notes, and reports related to the problems studied. The sources of data needed by researchers in this literature review are using primary sources and secondary sources. Data analysis aims to obtain answers from the formulation of the problem that has been determined, data analysis is carried out in an inductive and interpretive way. The result of this research is that the source of working memory during learning is explained in single-digit arithmetic learning, multi-digit arithmetic learning. Meanwhile, working memory in children with math difficulties is found in verbal working memory and visual-spatial working memory.